Colorimetric effect of Au nanoparticle chain/polymer film under mechanical stress and gas pressure - Shim, Gowoon; Eom, Kiryung; Lee, Gyuyeon; Seo, Hyungtak (Korean Journal of Materials Research, 2018)
Gas detection is necessary for various reasons, including the prevention of gas leakages and the creation of necessary environmental conditions. Among the gas detection methods, leakage of gas can be confirmed using materials that undergo color changes that are easily distinguished by the naked eye. Metal nanoparticles (NPs) experience variations in their absorption wavelengths under the localized surface plasmon effect (LSPR) with mechanical stresses, which change the distance between NPs. In this study, we attempted to detect the presence of gas utilizing the LSPR-related color change of a chain of Au NPs. The assembly of Au NPs, arranged in a chain shape, experienced a color change from dark blue to purple with a change in the distance between the NPs by applying a physical force, i.e., compression, stretching, and gas pressure. As the force of compression and the degree of stretching increased, the absorption wavelength shifted from doublet peaks at 650 and 550 nm to a singlet peak at 550 nm. Further, applying gas pressure caused an identical color change. With this result, we propose a method that could be applied to all gases that require detection based on gas pressure.
Keywords: Absorption wavelengths; Colorimetric; Environmental conditions; Gas detection methods; Gas pressures; Localized surface plasmon; Mechanical stress; Nanoparticle chains; Assembly; Au nanoparticles; Colorimetric; Gas pressure; Mechanical stress